(untitled) - Little, Jeffrey B. (New York, 2010)
A fully revised edition of the INVESTING CLASSIC For over 30 years this comprehensive, easy-to-read guide has served well as thedefinitive reference for successful investing. Now in its fifth edition and completelyupdated, Understanding Wall Street helps investors prosper in today's challengingeconomy whether you're just beginning or among the millions soon to retire. Understanding Wall Street, Fifth Edition, has new sections and information on theissues most important to today's investors, including How to use the Internet as an investing tool The shift to exchange traded funds (ETFs) The link between Wall Street and Main Street The Risks and rewards of the global economy Praise for previous editions of Understanding Wall Street Recommended. An excellent introduction to stock market intricacies. Booklist A lucid guide to those downtown mysteries. Newsday Remarkable . . . it remains as useful as ever . . . Experience may be the bestteacher, but this manual runs a close second. American Library Book Review.
Keywords: Stock exchanges,Investments,Stocks,Đầu tư,Cổ phần,Trao đổi cổ phần; United States,United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ